Introduction to Composite Function
In this Lesson, we will be looking at Composite function.
Let’s say we have a function f (x) = 2x + 3,
we can be asked to find f (2).
All we will do is to replace the x by the 2.
So we have
f(2) = 2 (2) + 3
f(2) = 7
Solving f(g(x)) - read as F of G of x
Let’s say we have another function
g(x) =x^2 + 1. We can be asked to find f (g(x)).
The same way we put the 2 in place of the x, we must put the g(x) in place of the x.
This becomes
f (g(x)) = 2 (g(x)) + 3.
Now we know what g(x) is, so we can put the x^2 + 1 to replace the g(x).
So we have
f (g(x)) = 2 (x^2 + 1) + 3. This is what composite function is all about.
Let’s expand this.
f (g(x)) = 2 x^2 + 2 + 3
f (g(x)) = 2x^2 + 5
Solving g(f(x)) - read as G of F of x
Now let’s do g(f(x)). We can write it this way to make it clearer. This time we are putting the f(x) in g(x).
g(f(x)) = (f(x))^2 + 1
We know that f(x) = 2x + 3. we put that in place of the f(x) to get
g(f(x)) = (2x + 3)^2 + 1
g(f(x)) = (2x + 3) (2x + 3) + 1
g(f(x)) = 4x^2 + 12x + 10
There is really no limit to how the question can be, but the idea is the same.
Solving f(f(x)) - read as F of F of x
Let’s do f(f(x)). We are putting f(x) back into f(x).
so we will have
f(f(x)) = 2 (2x + 3) + 3.
We can simplify to get
f(f(x)) = 4x + 9.
Solving f(g(3)) - read as F of G of 3
Let’s look at f(g(3). For a question like this, we will solve for the f(g(x) and then replace our x with 3.
We’ve already done f(g(x),
f (g(x)) = 2x^2 + 5
Let’s now put the 3 in place of the x.
f (g(3)) = 2(3)^2 + 5.
f (g(3)) = 23.
Let’s end this Lesson here. In the next Lesson, we will be looking at operations on functions. Have a great day. Good bye